Vehicle – pedestrian conflict: a case study in Universiti Putra Malaysia - Mohd Isa, Noorain; Aris, Ahmad Zaharin; Ponrahono, Zakiah; Harun, Rosta (Malaysian Institute of Planners, 2019)
Vehicle-pedestrian conflict is a commonly unsafe event that occurs in both urban and rural areas, especially in developing countries. It is still an open research topic, mostly in traffic safety and urban planning, which is utilised for evaluating the behaviours of vehicles and pedestrians at a non-signalised marked walkway. Three stations were selected based on higher daily activities to calculate the regularity of pedestrian movement. A manual calculation method was applied, and the calculation was done only during the daytime. Three different teams were formed to obtain the measurements at the three different sampling points simultaneously. A present study on preliminary vehicle-pedestrian conflict reveals the frequency of pedestrians in a concentrated area and its Level of Service (LOS) in Universiti Putra Malaysia (UPM) Serdang. The findings show that rush hour occurs during the mid-day in weekday, when students have finished their classes and adults have gone out for other businesses.